2009
DOI: 10.5216/ree.v10i2.8030
|View full text |Cite
|
Sign up to set email alerts
|

A reintegração de crianças e adolescentes institucionalizados vítimas de violência doméstica no espaço escolar

Abstract: A reintegração de crianças e adolescentes institucionalizados vítimas de violência doméstica no espaço escolar 1 Reintegration of institutionalized children and adolescents, victims of domestic violence into schoolLa reintegracción de niños y adolescentes institucionalizados víctimas de la violencia doméstica en el espacio escolar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
(10 reference statements)
0
2
0
3
Order By: Relevance
“…A study on school integration of child and adolescent victims of domestic violence observed that the denouncement of suspected cases of violence is not stimulated by the coordination of these institutions; teachers feel intimidated because of the posture of those hierarchically superior to them (18) . These data corroborate studies on the role of health professionals facing domestic violence against children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on school integration of child and adolescent victims of domestic violence observed that the denouncement of suspected cases of violence is not stimulated by the coordination of these institutions; teachers feel intimidated because of the posture of those hierarchically superior to them (18) . These data corroborate studies on the role of health professionals facing domestic violence against children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, nurses can develop strategies for adolescents involved in domestic violence and their families, knowing and accessing these networks through education and health care that promote autonomy and freedom for these individuals (8,21) . Primary prevention and health promotion of these individuals and their families; the awareness and recognition of the problem by professionals as inherent to the health sector; and coping with situations of violence by constructing interdisciplinary, interinstitutional and intersectoral interventions are the nursing category possibilities of approaching and appropriating of this debate (18)(19)(20) .…”
Section: Discussionmentioning
confidence: 99%
“…Dentre investigações encontradas na literatura científica e relacionadas à adolescência no contexto de acolhimento institucional no Brasil, antes, durante ou após este, encontra-se um amplo espectro de achados. Essas demonstram que adolescentes acolhidos podem experienciar problemas psicológicos e emocionais (Álvares & Lobato, 2013;Carlos, Ferriani, Silva, & Arone, 2008;Fernandes & Monteiro, 2016;Mota, Thomaz & Melo, 2015;Zappe, Moura Jr, Dell'Aglio, & Sarriera, 2013;Wathier & Dell'Aglio, 2007), contextos familiares fragilizados (Abaid & Dell'Aglio, 2014;Azôr & Vectore, 2008;Cruz, Pedroso, Cavalcante & Bucher-Maluschke, 2016), bem como sofrer com as problemáticas das próprias instituições (Carinhanha & Penna, 2012;Macedo, Pessoa & Alberto, 2015;Souza & Brito, 2015).…”
Section: A Adolescência Em Acolhimento Institucionalunclassified
“…A referida pesquisa, entretanto, permitiu dimensionar a exposição cotidiana desta população à violência CARLOS, 2007). A continuidade destes estudos levou à investigação da violência escolar sob o ponto de vista de alunos e funcionários, no município de Jardinópolis (SP) (FERRIANI et al, 2006), e à análise da inserção escolar de adolescentes vitimados e acolhidos institucionalmente, sob o ponto de vista destes sujeitos e de professores da rede pública de ensino, no município de Ribeirão Preto (SP) (CARLOS et al, 2008). Estes trabalhos demostraram que as instituições de atendimento à criança e ao adolescente, vítimas de violência doméstica, notadamente as instituições de acolhimento, além das escolas e dos serviços de saúde e de assistência social, não têm exercido o papel de proteção integral, conforme definido pelo ECA.…”
Section: Lista De Figurasunclassified